Molecular Mechanisms of Tungsten Toxicity Differ for Glycine max Depending on Nitrogen Regime - Preiner, Julian; Wienkoop, Stefanie; Weckwerth, Wolfram; Oburger, Eva (Frontiers in Plant Science, 2019)
Tungsten (W) finds increasing application in military, aviation and household appliance industry, opening new paths into the environment. Since W shares certain chemical properties with the essential plant micronutrient molybdenum (Mo), it is proposed to inhibit enzymatic activity of molybdoenzymes (e.g. nitrate reductase (NR)) by replacing the Mo-ion bound to the co-factor. Recent studies suggest that W, much like other heavy metals, also exerts toxicity on its own. To create a comprehensive picture of tungsten stress, this study investigated the effects of W on growth and metabolism of soybean (Glycine max), depending on plant nitrogen regime (nitrate fed (N fed) vs symbiotic N2 fixation (N fix)) by combining plant physiological data (biomass production, starch and nutrient content, N2 fixation, nitrate reductase activity) with root and nodule proteome data. Irrespective of N regime, NR activity and total N decreased with increasing W concentrations. Nodulation and therefore also N2 fixation strongly declined at high W concentrations, particularly in N fix plants. However, N2 fixation rate (g N fixed g-1 nodule dwt) remained unaffected by increasing W concentrations. Proteomic analysis revealed a strong decline in leghemoglobin and nitrogenase precursor levels (NifD), as well as an increase in abundance of proteins involved in secondary metabolism in N fix nodules. Taken together this indicates that, in contrast to the reported direct inhibition of NR, N2 fixation appears to be indirectly inhibited by a decrease in nitrogenase synthesis due to W induced changes in nodule oxygen levels of N fix plants. Besides N metabolism, plants exhibited a strong reduction of shoot (both N regimes) and root (N fed only) biomass, an imbalance in nutrient levels and a failure of carbon metabolic pathways accompanied by an accumulation of starch at high tungsten concentrations, independent of N-regime. Proteomic data (available via ProteomeXchange with identifier PXD010877) demonstrated that the response to high W concentrations was independent of nodule functionality and dominated by several peroxidases and other general stress related proteins. Based on an evaluation of several W responsive proteotypic peptides, we identified a set of protein markers of W stress and possible targets for improved stress tolerance.